Educating jurors about eyewitness testimony in criminal cases with circumstantial and forensic evidence. (July 2016) - Safer, Martin A.; Murphy, Ryan P.; Wise, Richard A.; Bussey, Logan; Millett, Cristina; Holfeld, Brett
Abstract: We investigated whether the Interview-Identification-Eyewitness factors (I-I-Eye) educational aid could sensitize mock jurors to the quality of eyewitness evidence in criminal cases which also contained circumstantial and forensic evidence. After participants were randomly assigned to read either the I-I-Eye or a control aid, they read a trial transcript containing either strong or weak eyewitness evidence. The police consistently followed scientific interviewing and identification procedures in the strong case, but not in the weak case. In two experiments, the I-I-Eye participants were approximately three times more likely than the control participants to enter guilty verdicts in the strong case than in the weak case. Thus the I-I-Eye educational aid increased participants' sensitivity to the eyewitness evidence. The I-I-Eye method provides a valuable analytical framework for evaluating eyewitness evidence in criminal cases. It may be capable of becoming "a standard feature for criminal cases" with eyewitness evidence.